2019
DOI: 10.4236/ojgas.2019.97015
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Treatment of Chronic Viral Hepatitis C by Direct-Acting Antivirals in Togo

Abstract: Background: Viral hepatitis C is the second leading cause of hepatocellular carcinoma after hepatitis B in Africa and Togo in particular. The advent of direct acting antivirals has revolutionized the care and prognosis of patients infected with hepatitis C virus (HCV). Objective: To evaluate the sustained virological response (SVR) 12 weeks after oral treatment without interferon in HCV infected patients with genotypes 1 and 2. Patients and Method: Descriptive and analytical study based on the retrospective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
1
Order By: Relevance
“…Wilder et al (2016) reported a similar SVR in black and non-black patients (95% vs 97%) with genotype 1 HCV infection. For HCV genotype 2, treatment with Sofosbuvir/Ledipasvir for 12 weeks was associated with elevated SVR rates in the study of Gane et al (2017) Hamadou et al, 2018;Coyer et al, 2020;Lawson-Ananissoh et al, 2019;Abozeid et al, 2018). A single-center study (Mairamou Hamadou et al, 2018) in Cameroon, 45/53 patients (84.9%) with HCV genotype 1 under Sofosbuvir/Ledipasvir  Ribavirin obtained an SVR, lower compared to our results.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Wilder et al (2016) reported a similar SVR in black and non-black patients (95% vs 97%) with genotype 1 HCV infection. For HCV genotype 2, treatment with Sofosbuvir/Ledipasvir for 12 weeks was associated with elevated SVR rates in the study of Gane et al (2017) Hamadou et al, 2018;Coyer et al, 2020;Lawson-Ananissoh et al, 2019;Abozeid et al, 2018). A single-center study (Mairamou Hamadou et al, 2018) in Cameroon, 45/53 patients (84.9%) with HCV genotype 1 under Sofosbuvir/Ledipasvir  Ribavirin obtained an SVR, lower compared to our results.…”
Section: Discussioncontrasting
confidence: 67%
“…Pangenotypic direct-acting antivirals are not easily accessible to populations in low-income countries (Spearman et al, 2019). The combinations Sofosbuvir/Ledipasvir  Ribavirin and Sofosbuvir/Ribavirin remain the most used in African patients infected with HCV genotypes 1 and 2 (Mairamou Hamadou et al, 2018;Coyer et al, 2020;Lawson-Ananissoh et al, 2019;Abozeid et al, J o u r n a l P r e -p r o o f 2018). The Sofosbuvir/Ribavirin combination, initially recommended in HCV genotype 2, is used less and less because of its low sustained virological response rate (SVR) in cirrhotic patients (Scott et al, 2018;AASLD-IDSA, 2020;EASL, 2018).…”
mentioning
confidence: 99%